Metacompetence As a University Education Goal - Robert KEBBEKUS (Communications of International Proceedings, 2024)
Companies and organizations increasingly require specialized professionals with wide-ranging and networked competencies (meta-competencies) in order to be able to react to dynamic framework conditions such as global changes and social trends. This study aims to identify didactic methods and learning content that support the development of skills among students in the social sciences in order to recognize, initiate and accompany transformation processes in social systems. This would enable universities to meet the growing demand of companies and organizations for specialists on the one hand and the desire for individual freedom and social participation of students on the other. The central question is: "What content and methods should students learn in order to be able to solve future problems and challenges in social systems?" In the current literature on higher education and learning, there are as yet no findings on which didactic and methodological learning content promotes skills that can demonstrably foster interventions in social systems. Methodologically, two types of qualitative data are collected: firstly, interviews with students before and after the educational project, and secondly, interview transcripts with representatives of companies and organizations as social systems. The data collected will be analyzed using qualitative content analysis according to Mayring and Clifford Geertz. The results so far indicate that, in addition to the didactic methods used, the freedom of the individual to satisfy their individual learning and skills development needs and the existence of a variety of skills within the group are essential for successful intervention in social systems.
Keywords: Capability approach; higher-education; social-system; social participation